Design and fabrication of polydimethylsiloxane based low cost microfluidic for ultra-fast diagnostic applications - Balakrishnan S.R.; Hashim U.; Sahrim M.; Ismail I.; Jamaludin J.; Ismail W.Z.W.; Perumal V.; Haarindraprasad R.; Mahalingam S. (Penerbit UTHM, 2023)
Diagnostic tools such as Point-of-Care (POC) analysis usually requires an on-site testing and measurements. Hence, to ease the fluid sample handling, microfluidics technology has been opted frequently to be incorporated with lab-on-chip (LOC). Therefore, an easy and conventional method of design and fabrication of the microfluidic device implemented. In this study, the device is fabricated with Polydimethylsiloxane (PDMS) and SU-8 using soft lithography technique. Herein, we focus on fluid transportation which is applied in clinical diagnostics and the transfer rate to the desired position as well as the fluid leakage during the transportation. Hence, the microfluidic sample transport channeling provides a practical solution for POC technological advances to study the biological systems that yield a better result in quantitative measurements and providing researchers new tools for life science research. Penerbit UTHM.